A study of brand equity and institutional image between two higher educational institutions - Lai, Huey Yih (2012)
ThiS study aims to investigate the brand equity and institutional image of two higher educational institutions to determine if there is a. difference between both variables between the two higher educational institutions. Apart from that, it is also the interest of the study to find out if there is a difference in parents' and students' view on brand equity and institutional image The results revealed that brand equity and institutional image between both institutions are different. Results also revealed that parents and students have different perception towards the brand equity and institutional image of institutions. Implications towards marketing of the institutions shall be considered .